Oral Behavior of Emulsified Systems with Different Particle Size and Thickening Agents Under Simulated Conditions - Arancibia-Aguilar, C; Riquelme-Hinojosa, N (Elsevier Ltd, 2021)
Food behavior during oral processing plays an essential role in the perception of texture. It depends on different factors, including food structure and composition, as well as its behavior when interacting with saliva. This study aimed to investigate the effect of particle size and thickener type of emulsified systems on physical, rheological, tribological, and oral oily coating properties under oral conditions. Six matrices based on oil-in-water emulsions with different particle sizes (NE-nanoemulsion and CE-conventional emulsions) were prepared using a mixture of emulsifiers (10% w/w) and sunflower oil (10% w/w). Thickened agents were added to the matrices (NE and CE) at different concentrations (3–4.5% w/w of starch-ST or 0.4–0.8% w/w xanthan gum-XG) to obtain equi-viscous samples (NE-EV) with their CE-based counterpart. Results showed a decrease in apparent viscosity values under oral conditions (saliva and shearing at 10 s−1) during the shear time, but this behavior was more evident in starch-based matrices. The lubrication properties of the different matrices depended mainly on the thickener concentration since equi-viscous samples (NE-ST-EV and NE-XG-EV) showed higher coefficient of friction (CoF) values. Finally, oral oily coating was more related to the oil droplets size than to the type of thickener since all NE-based matrices showed a higher amount of coating retained compared to the CE-based ones. Therefore, NE-based matrices could be used as an alternative to increase mouthfeel sensations in food emulsions. © 2021 Elsevier Ltd